Rheological indicators of wheat dough with the addition of lecithin and organic pumpkin seed meal flour for bakery products - Shevchenko, Anastasiia; Marynin, Andriy; Drobot, Vira; Shevchenko, Oleksandr; Kambulova, Yuliia (My University, 2025)
The aim of the study was to determine the influence of pumpkin seed meal flour mixed with phospholipids on the structural and mechanical properties of wheat flour dough. The particle size of wheat flour was mainly 119.7-135.4 µm, of pumpkin seed meal flour – 971.1-1242.0 µm and 196.0-221.6 µm. Wheat flour particles were characterized by an irregular, rather sharp shape with a wider surface. Pumpkin seed meal flour particles has larger size, a smooth surface, and many protein structures. The addition of lecithin to the recipe led to an increase in the storage modulus of the dough samples. It improved the elasticity of the dough. Replacing part of the wheat flour with pumpkin seed meal flour also increased the storage modulus and increased the deformation force necessary to break bonds and destroy such a dough system. The curves of the loss modulus also had an ascending character in proportion to the change in frequency. Replacing part of wheat flour with pumpkin seed meal flour in combination with lecithin changed the structural and mechanical properties of the dough system, such as elasticity and viscosity, resistance to deformation. Метою дослідження було визначення впливу борошна з гарбузового насіння, змішаного з фосфоліпідами, на структурні та механічні властивості тіста з пшеничного борошна. Розмір частинок пшеничного борошна становив переважно 119,7–135,4 мкм, а гарбузового борошна — 971,1–1242,0 мкм та 196,0–221,6 мкм. Частинки пшеничного борошна мали нерівну, досить гостру форму з ширшою поверхнею. Частинки гарбузового борошна були більшими за розміром, мали гладку поверхню та багато білкових структур. Додавання лецитину до рецептури призвело до збільшення модуля пружності зразків тіста. Це покращило еластичність тіста. Заміна частини пшеничного борошна борошном з гарбузового насіння також збільшила модуль пружності та збільшила силу деформації, необхідну для розриву зв'язків і руйнування такої тістової системи. Криві модуля втрат мали висхідний характер пропорційно до зміни частоти. Заміна частини пшеничного борошна борошном з гарбузового насіння в поєднанні з лецитином змінила структурні та механічні властивості тістової системи, такі як еластичність і в'язкість, опір деформації.
Keywords: кафедра технології хлібопекарських і кондитерських виробів; sunflower lecithin; grain size composition; surface morphology; rheological indicators; bakery dough; борошно з насіння гарбуза; соняшниковий лецитин; склад зерна; морфологія поверхні; реологічні показники; хлібопекарське тісто; хлібопекарське тісто